(untitled) (SAARC Journal of Agriculture, 2025)
The study was conducted at Sher-e-Bangla Agricultural University using eight advanced Brassica rapa L. populations to assess character variation, heritability, genetic advance, and correlations with seed yield per plant. ANOVA revealed significant variations among all populations for all the characters studied. High GCV and PCV were observed for the traits, including number of primary branches per plant, number of secondary branches per plant, number of siliquae per plant, and seed yield per plant. High heritability with high genetic advance was observed for plant height and number of siliquae per plant. Seed yield per plant showed a strong positive correlation with branches, root length, siliquae traits, and seed weight at both genotypic and phenotypic levels. Direct positive effects on per-plant seed yield were found in days to first flowering, plant height, number of siliquae per plant, and length of siliquae through path coefficient analysis. The highest per plant seed yield was observed in P3 (11.7g) followed by P4, P1, P6, and P5, with per-plant seed yields of 9.2g, 8.027g, 6.667g and 5.967g, respectively. Based on their higher per-plant yield potential and favorable combination of yield-contributing characters, five advanced populations- P3, P4, P1, P6, and P5- were selected from the eight. SAARC J. Agric., 23(1): 163-174 (2025)